Regional lymph node metastasis in colon adenocarcinoma - Maras, Gordan; Lindvall, Martin; Lundstrom, Claes (AIDA Data Hub, 2019)
Whole slide pathology images from regional lymph node metastasis in colon adenocarcinoma produced at Region Gävleborg Clinical Pathology and Cytology department and Region Östergötland Clinical Pathology department. Annotations for AI training produced as part of AIDA clinical fellowship project investigating AI decision support in metastasis detection. This dataset has been extended with a second collection series in the LNCO2 dataset using different collection and annotation parameters.
Keywords: Pathology; Whole slide imaging; Annotated; Lymph nodes; Cancer; Colon; Adenocarcinoma; Cancer and Oncology; Cancer och onkologi; Medical and Health Sciences; Medicin och hälsovetenskap